The ‘orphan implementations’ modality of public policy process for land resource distributions - Gertel Groome, Shulamith (Teorija in praksa, 2024)
A case study of land distributions establishing spatial arrangements for “new towns” in Israel is used to explore policymaking in an atmosphere of ethnocultural diversity and contention. Comprised of communities predisposed to conflict, the deeply divided Israeli public interest tends to draw ambiguous political declarations lacking clear operative directives. Data analyses show that the absence of directives may be advantageous to policy processes because it encourages flexible deference of decision-making to intermediate meso and local micro administrative levels. Emphasising the utility of flexible deliberative implementations initiated at bottom-up levels, it is hoped that the Orphan implementations of public policy modality for conflict/ambiguity issues can present a reconceptualised policy instrument. The article focuses on the verification and development of the modality in its capacity to provide a useful contribution to practical policy decisions wherever political attempts to consolidate fragmented public consensuses might be leveraged toward productive implementation. As such, we suggest that the aggregate outcome of bottom-up implementation initiatives over time may also have an affirming effect on the social balance of national spatial policy.
Keywords: bottom-up decision-making; delitev zemlje; implementacija politik; Javna politika; land distribution; land-use planning; načrtovanje rabe prostora; odločanje od spodaj navzgor; policy implementation; Politično odločanje; prostor; prostorska ureditev; prostorski konflikt; razporejanje zemljišč; Regionalno planiranje; space; spatial conflict